Miejsce ucznia zdolnego w praktyce dydaktycznej - Maria Porzucek-Miśkiewicz, Maria Porzucek-Miśkiewicz (Kultura-Społeczeństwo-Edukacja, 2018)
The aim of the thesis is to draw attention to issues related to gifted students, their needs and problems at school. The author reflects on the ways of satisfying the needs of a gifted student in the classroom. A gifted student is a person with special educational needs. Teachers in schools, which should take care of the development of each individual, often leave gifted students without assistance, as they believe that they will manage on their own. The author shows fragments of the Polish educational reality of gifted students.